HUBUNGAN TINGKAT DEPRESI PADA PASIEN LANJUT USIA DENGAN HIPERTENSI PRIMER DI RS DR. ESNAWAN ANTARIKSA HALIM PERDANAKUSUMA JAKARTA 2019 - Andriyanto Fadhli, (2019)
Depression is a one a major diseases in a geriatric. In a geriatric if a long time depression the body can to make adaption so appear pathological and organis disorders. A symptoms appear is hypertension. The aim of the research is a to identifity the relationship between depresion and hypertension on geriatric in Dr Esnawan Antariksa Halim Perdanakusuma's Hospital Jakarta This Research is a quantitative deskriptif analitic that used cross sectional design. Sample in this research a geriatric in Poliklinik Dr. Esnawan Antariksa Halim Perdanakusuma Hospital Jakarta were 58 respondens. Process sampling used Probability Purposive Sampling. Data analysis to used Chi Square. Based on analyzed Chi Square, there is a relationship between depresion and hypertension on geriatric in Dr. Esnawan Antariksa Halim Perdanakusuma Hospital Jakata were p value > 0, 05 that is 0, 041. There is a relationship between depresion and hypertension on geriatric in Dr. Esnawan Antariksa Halim Perdanakusuma Hospital's Jakarta. A Condition depression sympatic nerves increase to make hypertension stage.